Australia at war and peace - Summers, Sue; Oliver, Bobbie (Black Swan Press, 2014)
This chapter discusses the kinds of history generated by Australia’s experience in the wars of the 20th century. Despite monumental official histories of Australia’s involvement in the World Wars, scholarly and personal accounts of combatants, and revisionist studies of Australia’s military record, many gaps in the history remain. The goal of discussion is to return the public gaze to valid areas of enquiry that have been marginalised within mainstream historical research and media accounts of the past.